2006
DOI: 10.1126/science.1131988
|View full text |Cite
|
Sign up to set email alerts
|

Interface Mobility from Interface Random Walk

Abstract: Computational studies aimed at extracting interface mobilities require driving forces orders of magnitude higher than those occurring experimentally. We present a computational methodology that extracts the absolute interface mobility in the zero driving force limit by monitoring the one-dimensional random walk of the mean interface position along the interface normal. The method exploits a fluctuation-dissipation relation similar to the Stokes-Einstein relation, which relates the diffusion coefficient of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
121
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 22 publications
11
121
0
Order By: Relevance
“…Polycrystals are pervasive as engineering materials and elucidating mechanisms that determine the structure and dynamics of their GBs continue to be a central goal of materials research (9). Advances in computer simulation methods (2,10,11) and experiments (12,13) have provided substantial insights into the microscopic origins of these mechanisms. In conventional materials, nevertheless, establishing a direct link between the dynamics at the single/few atom length scale and the collective behavior of the many thousands of atoms that constitute GBs and grains poses a serious challenge (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polycrystals are pervasive as engineering materials and elucidating mechanisms that determine the structure and dynamics of their GBs continue to be a central goal of materials research (9). Advances in computer simulation methods (2,10,11) and experiments (12,13) have provided substantial insights into the microscopic origins of these mechanisms. In conventional materials, nevertheless, establishing a direct link between the dynamics at the single/few atom length scale and the collective behavior of the many thousands of atoms that constitute GBs and grains poses a serious challenge (14).…”
mentioning
confidence: 99%
“…Despite its technological relevance, the implications of kinetic roughening for GB mobility and grain growth remain poorly understood. Although molecular dynamics simulations can model atomistic phenomena realistically, they often are limited to small system sizes (19) and short time scales (11), which may influence measurements of GB roughness (15) and predictions of grain growth laws (2,20). Kinetic Monte Carlo simulations (21) and phase field models (22) are insensitive to microscopic details.…”
mentioning
confidence: 99%
“…At the particle level, it was observed a glassy type dynamics of the particles confined in the grain boundaries, due to transient caging of them by their nearest neighbors [59,60]. It has been seen, both by simulations [61] and experiments [62], how a grain boundary diffuses back and forth on a direction roughly perpendicular to the boundary, as if performing a one-dimensional random walk, although it was observed for short periods of time.…”
Section: Introductionmentioning
confidence: 86%
“…This mathematical development was validated with moleclular dynamics (MD) simulations of an initially flat grain boundary, with an attractive potential between the particles, and it was observed that the average interface position <h(t)> maintains a normal (Gaussian) distribution within each time interval considered [61]. It should be said, however, that their simulations were very short-what the MD simulations permitted-and lasted on the order of a few hundreds of picoseconds, corresponding to a movement of the mean interface position by several interatomic distances only.…”
Section: Grain Boundary Formation and Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation